The Major Soybean Allergen Gly m Bd 28K Induces Hypersensitivity Reactions in Mice Sensitized to Cow's Milk Proteins - Candreva, Ángela María (2016)
Reactions to soy have been reported in a proportion of patients with IgE-mediated cow’s milk allergy (CMA). In this work, we analyzed if Gly m Bd 28K/P28, one of the major soybean allergens, is a cross-reactive allergen with cow milk proteins (CMP). We showed that P28 was recognized by IgE sera from CMA patients and activated human peripheral basophils degranulation. Moreover, IgE sera of mice exclusively sensitized to CMP recognized P28. Splenocytes from sensitized animals secreted IL-5 and IL-13 when incubated with CMP or soy proteins, but only IL-13 when treated with P28. In addition, a skin test was strongly positive for CMP and weakly positive for P28. Remarkably, milk-sensitized mice showed hypersensitivity symptoms following sublingual challenge with P28 or CMP. With the use of bioinformatics’ tools seven putative cross-reactive epitopes were identified. In conclusion, using in vitro and in vivo tests we demonstrated that P28 is a novel cross-reactive allergen with CMP.